ANALISIS PERHITUNGAN TAKE OFF QUANTITY MELALUI METODE BIM (BUILDING INFORMATION MODELLING) PEKERJAAN STRUKTUR PROYEK GEDUNG KANTOR KEJAKSAAN NEGERI KOTA BALIKPAPAN - Nugroho, Tri Yulianto (INFO-TEKNIK, 2024)
BIM (Building Information Modeling) is a method that represents an integrated construction work that can save time and cost compared to conventional methods. In Indonesia, the application of BIM technology is very lacking and is still being developed. Through the Ministry of Public Works and Public Housing's policy No. 28 of 2018, it is the stage of BIM development in Indonesia where government buildings with an area of more than 2000 m2 over 2 floors are required to use BIM. This study aims to obtain a comparison of manual volume with BIM, the causes of the volume discrepancy, and how to evaluate the handling of the volume discrepancy that occurs. This research uses a case study on the construction project of the Balikpapan City Attorney's Office Building. The research method begins by collecting working drawings, detailed data on the calculation of the volume of work contract documents, manual calculations themselves, daily reports, job documentation, and interviews. This research uses Revit and Cubicost BIM software to perform 3D modeling. 3D modeling uses working drawing data with output in the form of taking quantity data for casting, reinforcement, formwork, and steel fabrication work. The volume data from the take of quantity will be used as a reference for comparison with the manual calculation method and the factors causing the difference will be analyzed using the Pareto and fishbone methods. From the results of the analysis, it is found that the deviation of the BIM calculation manually is 95.49 m3, 16,358 Kg of iron, 280.39 m2 of formwork, and 56.08 Kg of steel fabrication with a total cost of Rp. 563,082,794.00. The large deviation of the project BOQ with BIM is foundry work of 131.63 m3, 36,675 Kg of iron, 1261.7 m2 of formwork, and 1102.7 Kg of steel fabrication with a total cost of Rp. 1,401,595.553.00. The most dominant risk of miscalculation with a cumulative value of 80% is iron (columns, plates, beams) and formwork (plates, beams, stairs). The cause of the difference in volume is due to the lack of detailed working drawings that apply the manual 2D draft method and the calculation process that is often overlooked and incomplete. Solutions and evaluations that need to be carried out are the need for expert certification of workers and the implementation of BIM at every stage of construction.